Exploring the Photophysical Properties of Some Dextran-Iron Oxide Nanoparticle Composites - Ion Lungu; Tamara Potlog; Anton Airinei; Radu Tigoianu; Carmen Gherasim (Molecules)
In this study, we report the synthesis and characterization of Fe3O4 nanoparticles coated with dextran. The structural and optical properties of the Dx:Fe3O4 synthesized composites were investigated by Fourier Transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and UV–Vis absorption spectroscopy. For the first time in this paper, the photophysics of Dx:Fe3O4 composites in water is studied using fluorescence and phosphorescence molecular spectrometry. An analysis of the absorption spectra of the Dx:Fe3O4 composite reveals the broad absorption bands with maxima at wavelengths of 227 nm, 264 nm, and 340 nm. Dx:Fe3O4 composite nanoparticles in water exhibit strong fluorescence with a quantum yield of 0.24% in contrast to 0.07% for dextran. Phosphorescence spectra confirm the formation of new emission bands within the Dx:Fe3O4 solution evidenced by the maxima shift for both dextran and Dx:Fe3O4 composites.